An efficient synthesis of 2-thio-5-amino substituted benzoquinones via KI catalyzed cascade oxidation/Michael addition/oxidation starting from hydroquinone. Issue 14 (27th January 2016) - Lu, Yihuan; Zhao, Yuqiong; Wang, Shucheng; Wang, Xin; Ge, Zemei; Li, Runtao
Abstract : An efficient one-pot approach to 2-thio-5-amino substituted benzoquinones has been developed. The use of S-alkylisothiouronium salts as thiol equivalents is more convenient and environmental friendly. Abstract : A simple and efficient synthesis of 2-thio-5-amino substituted benzoquinones via KI catalyzed cascade oxidation/ S -Michael addition/oxidation/ N -Michael addition/oxidation starting from hydroquinone, amines and S -alkylisothiouronium salts was described. Various 2-thio-5-amino substituted benzoquinones were obtained by this method in moderate to good yields. The use of S -alkylisothiouronium salts as thiol equivalents is more convenient and environmental friendly.